2020
DOI: 10.1149/1945-7111/abb1d4
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Nitrogen-Doped Nano-Crystalline Graphite Thin Films and Their Application as Electrochemical Sensors

Abstract: Herein, several nitrogen-doped nano-crystalline graphite films (N-NCG) were prepared via plasma-enhanced chemical vapor deposition (PECVD); nano-crystalline graphite (NCG) was doped by adding ammonia gas during the PECVD growth. To develop electrochemical probes that can compete with glassy carbon (GC) electrodes for anthracene sensing, the N-NCG electrodes were systematically investigated using different techniques, including atomic force microscopy (AFM), X-ray diffraction (XRD), X-ray photoelectron spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The deposition technique offers the advantage of growing the films directly on an insulating layer (i.e., SiO ), thus eliminating the need for an ulterior transfer step, which, for example, is required for the SLG thin films. The bulk-NCG thin films are grown with a previously established process [ 37 , 38 , 39 ], in a CH :H (60:75 sccm) atmosphere, at a pressure of 200 Pa and an RF discharge power of 100 W. The substrate temperature is kept at a high value of 890–900 °C, over a two h plasma growth step, to promote a high nucleation density. This in turn will result in thin films with high edge defect density, which is beneficial for sensors that rely on conductivity variations due to particle surface adsorption [ 37 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deposition technique offers the advantage of growing the films directly on an insulating layer (i.e., SiO ), thus eliminating the need for an ulterior transfer step, which, for example, is required for the SLG thin films. The bulk-NCG thin films are grown with a previously established process [ 37 , 38 , 39 ], in a CH :H (60:75 sccm) atmosphere, at a pressure of 200 Pa and an RF discharge power of 100 W. The substrate temperature is kept at a high value of 890–900 °C, over a two h plasma growth step, to promote a high nucleation density. This in turn will result in thin films with high edge defect density, which is beneficial for sensors that rely on conductivity variations due to particle surface adsorption [ 37 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The bulk-NCG thin films are grown with a previously established process [ 37 , 38 , 39 ], in a CH :H (60:75 sccm) atmosphere, at a pressure of 200 Pa and an RF discharge power of 100 W. The substrate temperature is kept at a high value of 890–900 °C, over a two h plasma growth step, to promote a high nucleation density. This in turn will result in thin films with high edge defect density, which is beneficial for sensors that rely on conductivity variations due to particle surface adsorption [ 37 ]. The PECVD process yields bulk-NCG thin films of ≊360–380 nm thickness with a conductivity of over S m [ 38 , 39 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Several nitrogen-doped nano-crystalline graphite films (N-NCG) were grown directly on a silicon substrate, using plasma-enhanced chemical vapor deposition (PECVD), and the electrochemical behavior had been compared with the conventional glassy carbon (GC) electrode. 26 The authors demonstrated improved features of the N-NCG electrodes by introducing different NH 3 flow rates (3, 5, and 7 sccm) during the PECVD growth of N-NCG film. The N-NCG films thickness decreased from ∼284 nm (N-NCG 3) to ∼135 nm (N-NCG 5) and ultimately reached ∼99 nm (N-NCG 7).…”
Section: The Microfabrication and Applications Of Amperometric Devicesmentioning
confidence: 99%
“…Amperometric sensors.-Amperometric microfabricated three electrode systems are a very good alternative for integrated electrochemical device, due to the fact that they are more stable than flexible electrochemical devices, and they are not disposable device like the integrated electrodes from the screen-printed family, where the ink is exfoliating when subjected to a cleaning procedure. In the last decade, electrochemical microfabricated electrodes (Table I) have been intensively used for the determination of heavy-metals, 16,[21][22][23][24][25]27 pollutants, 26,[28][29][30] drugs, 31,32,37 biomolecules, 35,39 oxygen 33 and hydrogen peroxide. 34 In 2010, Chen et al 21 proposed a microfabricated on-chip goldsilver-gold (Au-Ag-Au) three-electrode system for the determination of mercury ions.…”
Section: The Microfabrication and Applications Of Amperometric Devicesmentioning
confidence: 99%
“…Raman analysis of sp 2 bonded carbon nanostructures, such as ours, is typically conducted in the visible spectral range. Nevertheless, we thought it would be interesting to analyse the Raman response of our samples with a 325 nm He-Cd laser, as numerous investigations in the visible spectral range of this type of carbonic film have already been published [4][5][6]22]. Although the UV excitation causes dispersion of the D band and may suppress its intensity [23][24][25][26], the acquired spectra can still be utilised as a qualitative comparison of each sample's crystallinity relative to each other.…”
Section: Raman Spectroscopymentioning
confidence: 99%